The empowered manager positive political skills at work - Block, Peter (Wiley, 2016)
This book shows you how a new approach to management empowers all employees at all levels, and culminates in better business outcomes for the entire organization. Help shape a culture of commitment Develop the political skills to negotiate successfully Take responsibility for your actions Learn to fail up, and face setbacks with courage If you feel controlled by bureaucracy, unrewarded for creativity, and from a distance, powerless to control your own destiny, this book is the breath of fresh air your career has been craving. Timeless tips from a master of business strategy alongside a framework for more effective management makes The Empowered Manager a must-read guide for anyone doing business today"--